Plasma osteoprotegerin predicts adverse cardiovascular events in stable coronary artery disease: the PEACE trial - Ma, Teng; Zhao, Jian; Yan, Yechao; Liu, Junying; Zang, Jie; Zhang, Yaqi; Ruan, Kun; Xu, Hong; He, Wan (Frontiers in Cardiovascular Medicine, 2023)
Background: Osteoprotegerin (OPG) is a secretory glycoprotein and participates in the progression of atherosclerotic lesions. We aim to explore the relationship between OPG and the progression of coronary artery disease (CAD). Methods: OPG concentrations were measured in 3766 patients with stable CAD who were enrolled in the PEACE trial. The PEACE trial group followed them and examined future clinical events. Results: In total, 208 (5.5%) primary outcomes occurred, 295 (7.8%) died from all-cause death, 128 (3.4%) died from cardiovascular causes and 94 (2.5%) experienced heart failure during a median follow-up of 1892 days. Higher levels of OPG were associated with higher rates of all-cause death, cardiovascular death and heart failure, even after adjusting clinical cofounders. Conclusion: We demonstrated that elevated plasma OPG levels were associated an increased risk of all-cause death, cardiovascular death and heart failure in patients with stable CAD.